AB0971 LONG-TERM EFFICACY AND SAFETY OF CANAKINUMAB IN PATIENTS WITH SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS: RESULTS FROM A SINGLE-CENTER STUDY. (2nd June 2020) - Alexeeva, E.; Krekhova, E.; Dvoryakovskaya, T.; Isaeva, K.; Chomakhidze, A.; Chistyakova, E.; Lomakina, O.; Denisova, R.; Mamutova, A.; Fetisova, A.; Gautier, M.; Vankova, D.; et al.
Abstract : Background: Results from various phase 3 clinical studies have demonstrated the efficacy of canakinumab to treat patients with systemic juvenile idiopathic arthirtis (sJIA). However, limited information is available on the long-term efficacy and safety of this drug to treat children with sJIA. Objectives: To evaluate the long-term efficacy and safety of canakinumab in patients with sJIA treated at the National Medical Research Center of Children`s health, Moscow, Russia. Methods: This was a prospective, single-center study that included canakinumab (CAN)-naive patients diagnosed with sJIA following the International League of Associations for Rheumatology (ILAR) criteria and start receiving CAN treatment from 10/2012 to 03/2016. Patients included in this study also participated, for defined periods of time, in the clinical trial NCT02296424 . Patients with active disease started treatment with canakinumab 4 mg/kg. A treat-to-target approach was used, canakinumab was discontinued in patients on clinical remission, either following the NCT02296424 protocol or by investigator's decision, and re-introduced in those patients who experienced a relapse afterwards. Disease characteristics and demographics were recorded at the time of diagnosis and initiation of treatment (study entry). Disease activity was evaluated periodically using the adapted JIA ACR core set measures, and percentages of patients with inactive disease and on clinical remission were calculated using the sJIA ACR criteria. Response to treatment was also evaluated by calculating modified ACR responses and JADAS-71 scores. Safety was assessed by collecting and classifying adverse events (AEs) at each visit. Results: Nineteen patients presenting with sJIA were included in this study, with a median age at treatment initiation of 9.6 (interquartile range, IQR 6.4-11.1) years and a median disease duration of 4.4 (IQR 1.2-7.0) years. Most patients (17/19) had been treated previously with one or more biologic agents for sJIA. As of 23 December of 2019, the median time of follow up was 55.5 (47-71.7) months, with all patients being followed for at least 3.5 years and 5 patients followed for more than 7 years. As it is shown in figure 1, most patients (16/19) were on clinical remission one year after starting therapy, and this effect was sustained at year 3.5 (17/19). ACR 90 responses were observed in 84.2% (16/19) patients at one year and 94.7% (18/19) patients at 3.5 years, whereas JADAS-71 scores decreased from 15 (14: 28.5) at baseline to 0 (0: 0) at one year with 4/19 patients maintained with JADAS-71 >0); at 3.5 years, only one patient had JADAS-71>0 (0.47, due to slight ESR increasing). Concerning the 5 patients with >7 years of follow up, three of them were in clinical remission for more than 3 years, including one who had discontinued therapy more than 2 years. Another patient had a relapse after attempting drug discontinuation, but recovered clinical remission after reintroducing canakinumab, and remained in this state for the last two years. The remaining patient has persistent low levels of disease activity during the last four years of follow up. AEs required hospitalization were reported in 36.8% (7/19) patients. Conclusion: Sustained clinical remission was observed in most patients with sJIA treated with canakinumab for up to 7 years, with no new or unexpected adverse events reported. Disclosure of Interests: Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Elizaveta Krekhova: None declared, Tatyana Dvoryakovskaya: None declared, Ksenia Isaeva: None declared, Aleksandra Chomakhidze: None declared, Evgeniya Chistyakova: None declared, Olga Lomakina: None declared, Rina Denisova: None declared, Anna Mamutova: None declared, Anna Fetisova: None declared, Marina Gautier: None declared, Dariya Vankova: None declared, Meyri Shingarova: None declared, Ivan Kriulin: None declared, Alina Alshevskaya: None declared, Andrey Moskalev: None declared